The Relationship Of Obesity Nutritional Status And Physical Activity With Menstrual Cycle In Female Students In The Department Of Nutrition Poltekkes Surabaya - Zian Nur Afidah; Taufiqurrahman; Eny Sayuningsih; Erlyna Jayeng Wijayanti (Politeknik Kesehatan Kemenkes Surabaya, 2023)
One of the effects of obesity is irregular menstrual cycles. In addition to obesity, menstrual regularity can be affected by physical activity. The aim of the study was to determine the relationship between obesity nutritional status and physical activity with the menstrual cycle in female students of the Department of Nutrition, Poltekkes Surabaya. Methods: Analytic observational research using a cross sectional approach. Data collection by measuring body weight, height, menstrual cycle interviews, and physical activity interviews used the PAL Questionnaire. The number of samples is 55 female students with simple random technique. Assessment of nutritional status using the BMI index. Statistical test using the Spearman test. The results showed that the highest frequency of respondents with nutritional status was not obese (78.2%), light physical activity (94.5%), and had normal menstrual cycles (70.9%). Statistical test between obesity nutritional status and menstrual cycle (p=0.074), physical activity and menstrual cycle (p=0.262). This study shows that there is a relationship between obesity nutritional status and the menstrual cycle and there is no relationship between physical activity and the menstrual cycle in female students of the Department of Nutrition, Poltekkes Surabaya.